Law Enforcement Against Criminal Acts Local Elections by Gakkumdu - Muslihannisa Muslihannisa; Ismansyah Ismansyah; Nani Mulyati (International Journal Labs, 2023)
The election of the Regional Head of Padang Pariaman Regency as a form of democracy must be carried out in accordance with the provisions of the legislation, but in the process of its implementation it cannot be separated from various actions that can harm a lot of people, and the integrity of the implementation of the Regional Election. In this case, the integrated law enforcement center (Gakkumdu) enforces the law on the crime of regional head elections. The research method used in this study is empirical juridical. Based on the results of the study, it can be concluded: Law enforcement against criminal acts of integrated law enforcement centers in handling criminal acts for the election of the head of Padang Pariaman region is ineffective because of the 3 (three) findings of criminal cases handled there are no cases has reached the court level, all cases stop on the second discussion of Sentra Gakkumdu. The obstacles faced in law enforcement of criminal acts are associated with factors that affect law enforcement consisting of 5 (five) namely legal factors, law enforcement, facilities and facilities, society, and culture. To overcome obstacles by the integrated law enforcement center in law enforcement of regional election crimes is to carry out its duties as a law enforcement holder without any internal and external influence of a policy with the aim that the democratic process runs with the creation of justice, safely, and peacefully.